Influence of frequency and cutting height on some regrowth characteristics of andropogon grass - Drudi, Ary; Favoretto, Vanildo; Reis, Ricardo Andrade (Pesquisa Agropecuaria Brasileira, 2014)
This experiment was carried out at Faculdade de Ciências Agrárias e Veterinárias of UNESP, Campus de Jaboticabal, SP, Brazil, to evaluate the best management of Andropogon grass (Andropogon gayanus Kunth var. bisquamulatus (Hochst.) Hack). A factorial arrangement consisting of three cutting heights (10 cm, 20cm and 30cm above ground), two cutting frequencies (35 and 42 days) and four cutting dates were studied in a randomized block design. Regrowth vigor was not affected by cutting frequencies and heights, but it was greater during the two first cutting dates. At these dates the percentage of decapitated tillers was smaller too. Late elevation of the growing points was observed during the experimental period. Stem bases showed tendency to accumulate more total nonstructural carbohydrates (TNC) than roots. These components decreased during the first seven days after each cutting showing that carbohydrates were being used in regrowth. TNC contents were recovered 21 days after cutting.